Scottish nationalist leaflets, 1844-1973. - Scottish National Party (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2016)
Many of these pamphlets were printed by the Scottish National Party or the party that it came before it. Authors include Archie Lamont, Hugh Macdiarmid, and William Mitchell. These items contain research and policy proposals for how an independent Scotland might manage financially. They also contain both a pamphlet of nationalist songs and a history of the nationalist movement which was printed in 1853. The idea of using of oil wealth to support an independent Scotland can be traced back to the 1970s. Questions about how the European Union might affect independence also date back to these papers.
Date range: 1844-1973.
Keywords: Nationalism -- Scotland -- History; Scotland -- Politics and government -- 19th century; Scotland -- Politics and government -- 20th century